Nonperturbative approach to superfluid bose systems - Peletminskii, A.S.; Peletminskii, S.V.; Poluektov, Yu.M. (Вопросы атомной науки и техники, 2012)
We study a superfluid Bose system with single-particle and pair condensates using a nonperturbative approach. The self-consistency equations for two order parameters are obtained from the principle of maximum entropy. They are analyzed numerically at zero temperature for dilute (gases of alkali-metal atoms) and dense (superfluid ⁴He) systems. It is shown that the pair condensate fraction is negligible for dilute systems and becomes dominant for dense systems. На основе непертурбативного подхода изучается сверхтекучая бозе-система с одночастичным и парным конденсатами. Из принципа максимума энтропии найдены уравнения самосогласования для двух параметров порядка. Они проанализированы численно при нулевой температуре для разреженных (газы атомов щелочных металлов) и плотных (сверхтекучий ⁴He) систем. Показано, что доля парного конденсата пренебрежимо мала для разреженных систем и становится преобладающей для плотных. На основі непертурбативного підходу вивчається надплинна бозе-система з одночастинковим та парним конденсатами. Із принципу максимуму ентропії здобуто рівняння самоузгодження для двох параметрів порядку. Їх проаналізовано чисельно при нульовий температурі для розріджених (гази атомів лужних металів) та густих (надплинний ⁴He) систем. Показано, що частка парного конденсату є нехтовно малою для розріджених систем і стає переважною для густих систем.